Emas Hijau dan Biru dari Jerowaru: Mengangkat Ekonomi Warga Pesisir Melalui Rumput Laut dan Lobster - Yazid Syahram; Haekal Hakim (Lembaga Publikasi Ilmiah Nusantara, 2026)
Jerowaru District, located in East Lombok Regency, possesses extraordinary marine potential, particularly in the development of superior commodities such as seaweed, nicknamed